2021
DOI: 10.3390/diagnostics11122366
|View full text |Cite
|
Sign up to set email alerts
|

The Summarized Assessment of Endothelin A Receptor Expression in Renal Transplant Compartments Associated with Antibody-Mediated Rejection

Abstract: The occurrence of anti-endothelin A receptor antibodies may be useful in diagnosis of transplant damage. We noticed that the presence of the endothelin A receptor (ETA receptor) in biopsy compartments is yet to be defined. We decided therefore to analysed the presence and relevance of the ETA receptor in biopsy to define the cause. Our study aims to evaluate the expression of ETA receptors in renal recipients after a biopsy due to the worsening of transplant function. Methods: The expression of ETA receptors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As mentioned above, it is crucial to pursue new ways of protecting transplanted organs. As a matter of fact, antibody-mediated rejection is the leading player in graft immunological injury and transplant loss, with the massive significance of human leukocyte antigen and the anti-HLA and non-HLA antibodies [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Recent studies have shown that especially the non-HLA antibodies, including anti-ETAR antibodies, should be pursued, as their importance is being revealed [ 89 ].…”
Section: The Role Of Ido1 In Kidney Allograftsmentioning
confidence: 99%
“…As mentioned above, it is crucial to pursue new ways of protecting transplanted organs. As a matter of fact, antibody-mediated rejection is the leading player in graft immunological injury and transplant loss, with the massive significance of human leukocyte antigen and the anti-HLA and non-HLA antibodies [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Recent studies have shown that especially the non-HLA antibodies, including anti-ETAR antibodies, should be pursued, as their importance is being revealed [ 89 ].…”
Section: The Role Of Ido1 In Kidney Allograftsmentioning
confidence: 99%
“…Moreover, the study has shown a significant association between the AT1R-Ab positivity and positivity for Ab against the endothelin A type 1 receptor (ETAR-Ab) [ 37 ]. Researchers pointed out the need to perform a prospective study regarding high prevalence of AT1R-Ab pre-transplant and its association with TCMR and possible treatment methods in such patients.…”
Section: The Impact Of Abmr Coincidence On the Ca Tcmr Prognosismentioning
confidence: 99%
“…The endothelium of preglomerular vessels expresses endothelin subtype A receptor (ETAR) 3 and angiotensin II type I receptor (AT1R) at substantially low levels in glomerular endothelial cells 1 . ETAR is highly expressed in the tubular epithelium compared with that in the glomerulus; ETAR positivity in the glomeruli is associated with a high risk of AMR, 4 and the occurrence of graft loss has been reported 5 . This is because the increase in ETAR expression is associated with a reduction in tissue integrity 6 and an increase in autoantibody‐binding capacity 7 .…”
Section: Introductionmentioning
confidence: 99%